Self-reported secure and insecure cyber behaviour: factor structure and associations with personality factors. Issue 3 (1st October 2017) - Russell, Justin D; Weems, Carl F; Ahmed, Irfan; Richard III, Golden G.
ABSTRACT: The present study provides initial data on self-reported secure and insecure cyber behaviour using the iSECURE. A theoretical model for item pool development, distributions and convergent associations is presented. Data on the distribution of self-report of secure and insecure cyber behaviour is presented as well as data on factor structure of scores collected from a sample of 210 college-age adults (56.7% female). Exploratory factor analysis indicated a two-factor solution, with items loading onto subscales of secure or unsecure cyber behaviour. Comparison with an existing measure of attitudes about cyber security suggested good convergent validity. Additional analyses examined correlations between the iSECURE and Big Five personality traits as well as other personality and behavioural characteristics. The distribution of responses suggests that self-report may be useful in research studies that attempt to build towards predicting actual behaviour. The implications of findings for future research are discussed in terms of the need to develop additional techniques such as the use of real-world scenarios.